Evaluating When and Why Patients Discontinue Chronic Therapy for Irritable Bowel Syndrome With Constipation and Chronic Idiopathic Constipation. (4th February 2020) - Shah, Eric D.; Suresh, Suraj; Jou, Jessica; Chey, William D.; Stidham, Ryan W.
Abstract : INTRODUCTION: To inform the patient-centered discussion regarding comparative outcomes with irritable bowel syndrome/chronic idiopathic constipation pharmacotherapy, we evaluated reasons and timing of discontinuation of FDA-approved pharmacotherapy for irritable bowel syndrome and chronic idiopathic constipation in a large observational real-world cohort. METHODS: We identified patients initiating lubiprostone or linaclotide within the University of Michigan Electronic Medical Record (2012–2016). Medication start and stop dates were determined in manual chart review including detailed review of all documentation including office notes and telephone encounters. A Cox model was constructed to predict the hazard of discontinuation. RESULTS: On multivariate analysis of 1, 612 patients, linaclotide users had a lower risk of discontinuing therapy than lubiprostone users for any reason (hazard ratio [HR] = 0.6, 95% confidence interval [CI] 0.5–0.8). At 3 and 12 months, the overall discontinuation rates were 23% and 43% for lubiprostone compared with 14% and 24% for linaclotide. Over the first year of therapy, more than half of discontinuations due to intolerance occurred in the first 3 months for both drugs. Linaclotide users were more likely to discontinue due to intolerance (HR = 1.6 [95% CI, 1.2–2.3]) but less likely to discontinue due to insufficient efficacy of therapy (HR = 0.5 [95% CI, 0.4–0.8]). IBS diagnosis increased the hazard of discontinuation of lubiprostone relative to linactolide (HR = 1.4, 95% CI, 1.1–1.6). Loss of prescription drug coverage remained a common reason for discontinuation over the first year of therapy. DISCUSSION: Individuals appear more likely to discontinue lubiprostone than linaclotide overall, but more likely to discontinue linaclotide compared with lubiprostone due to intolerance (mostly diarrhea). Most discontinuations due to intolerance occur in the first 3 months. These results may be useful in individualized treatment selection and enhancing patient knowledge regarding long-term outcomes.